Association of Coronary Artery Anatomical Variations with Myocardial Fibrosis and Interventional Outcomes - Khatoon, Shehla; Halima, Amna; Rehman, Zainab; Abubakkar, Sayyed; Hayat, Sikandar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Coronary artery anatomical variations are frequently encountered during diagnostic coronary angiography and interventional cardiac procedures. Although traditionally considered incidental, emerging evidence suggests that altered coronary anatomy may influence myocardial perfusion and contribute to subclinical myocardial remodeling. Myocardial fibrosis represents an early marker of adverse myocardial change and carries important prognostic implications. Objective: To evaluate the association between coronary artery anatomical variations, myocardial fibrosis, and interventional outcomes in patients undergoing coronary angiography. Methodology: This prospective observational study was conducted at the Department of Cardiology, Peshawar Institute of Cardiology, from January 2022 to January 2023. A total of 120 adult patients undergoing clinically indicated coronary angiography were consecutively enrolled. Coronary anatomical variations including dominance patterns, myocardial bridging, anomalous coronary origins, coronary tortuosity, and luminal stenosis were documented. Myocardial fibrosis was assessed using cardiac magnetic resonance imaging and surrogate functional parameters. Interventional outcomes were correlated with underlying anatomical variations. Statistical analysis was performed using chi-square tests and multivariate logistic regression. Results: Myocardial fibrosis was detected in 43.3% of patients. Myocardial bridging, anomalous coronary origins, coronary tortuosity, and significant luminal stenosis were significantly associated with myocardial fibrosis (p < 0.05). Patients with anatomical variations demonstrated significantly higher rates of percutaneous coronary intervention, multi-vessel revascularization, increased procedural complexity, and peri-procedural ischemic changes. Conclusion: Coronary artery anatomical variations are significantly associated with myocardial fibrosis and adversely influence interventional outcomes. Recognition of these variations may enhance risk stratification and guide individualized interventional planning.